2022
DOI: 10.5455/ovj.2022.v12.i6.10
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal obstruction due to trichobezoar in a she-camel (Camelus dromedarius)

Abstract: This report describes oesophageal obstruction in camel due to trichobezoar. She camel of two-year-old presented to Veterinary Teaching Hospital, King Faisal University, with a history of inability to swallow and there was food and water regurgitation for one day before. Palpation revealed clear visible mass on neck region about 105 cm caudal to the head. Radiography and endoscopic examination revealed an oval-shaped foreign body embedded in the oesophageal lumen in the level distal third of neck. The foreign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(22 reference statements)
1
1
0
Order By: Relevance
“…This was possibly related to nutritional deficiencies and mineral imbalances, especially trace elements and poor farming and hygiene in grazing areas. These findings conformed to the previous studies [ 5 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…This was possibly related to nutritional deficiencies and mineral imbalances, especially trace elements and poor farming and hygiene in grazing areas. These findings conformed to the previous studies [ 5 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…In this particular case, the presence of foreign objects composed of hairy material was found; therefore, they were considered trichobezoars (hair balls). This condition has been reported in different animal species, including camels, 13 buffaloes, 14 cattle 15 and small ruminants 16 . However, the presence of trichobezoars in sheep is not common, a study conducted in the semi‐arid region of Nigeria indicated that out of 540 animals studied postmortem, only 7.4% had trichobezoars 17 .…”
Section: Discussionmentioning
confidence: 99%